MODELOS DE REGRESSÃO BETA E SIMPLEX NA ANÁLISE DO ÍNDICE DE DESENVOLVIMENTO HUMANO MUNICIPAL DE 2010 - MENEZES, André Felipe Berdusco; FURRIEL, Wesley Oliveira (Brazilian Journal of Biometrics, 2019)
The goal of this paper was to investigate the MHDI of 2010 from some indicators of socioeconomic and spacial, in order to nd out the existence of relationships between them. To this end, descriptive statistics techniques were applied to visualize the data behavior and the Beta and Simplex regression models, which are appropriate to modeling rates and proportions, were employed in order to measure and evaluate the impact of covariates on the human development index of Brazilian cities. The results showed that the models presented estimates and conclusions quite similar, in respect of the mean regression structure. Furthermore, it was observed a considerable accordance among the social indicators selected and the response variable.